2020
DOI: 10.1007/s10103-020-03189-7
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo study of Ho:YAG and thulium fiber lasers for soft tissue surgery: which laser for which case?

Abstract: The goal of this study was to assess the ablation, coagulation, and carbonization characteristics of the holmium:YAG (Ho:YAG) laser and thulium fiber lasers (TFL). The Ho:YAG laser (100 W av.power), the quasi-continuous (QCW) TFL (120 W av.power), and the SuperPulsed (SP) TFL (50 W av.power) were compared on a non-frozen porcine kidney. To control the cutting speed (2 or 5 mm/s), an XY translation stage was used. The Ho:YAG was tested using E = 1.5 J and P av = 40 W or P av = 70 W settings. The TFL was tested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…Thus, the tissue penetration depth is 0.2 mm. In vitro studies reported higher incision and coagulation depths in continuous wave mode in comparison to the pulsed one [20][21][22]. At the same power output, a pronounced carbonization was reported in continuous wave mode.…”
Section: Key Pointsmentioning
confidence: 90%
“…Thus, the tissue penetration depth is 0.2 mm. In vitro studies reported higher incision and coagulation depths in continuous wave mode in comparison to the pulsed one [20][21][22]. At the same power output, a pronounced carbonization was reported in continuous wave mode.…”
Section: Key Pointsmentioning
confidence: 90%
“…As a potential consequence to the longer pulse duration, the morphology and the duration of the induced vapor channel created at the fiber tip could participate in the smaller ODV for Tm-Fiber [ 5 ]. If the mechanism of stone ablation associates photothermal and mechanical effects, the induced vapor bubbles take parts in both mechanisms [ 19 , 20 , 21 ]. A longer (duration and size) and wider bubble flow may be responsible for a greater ablated volume in a precise location, thereby reducing the ODV, according to our definition.…”
Section: Discussionmentioning
confidence: 99%
“…Continuous temperature increases above 60 o C and above the boiling point lead to tissue ablation/vaporization [7]. A further increase in temperature leads to the onset of pyrolysis, which eventually terminates in carbonization [18].…”
Section: Absorption In Watermentioning
confidence: 99%